The French Personalism and Critical Philosophy of History - Radžvilas, Vytautas (Problemos, 1985)
Based upon materials of the French personalism a study is conducted of the link between the traditional Christian historiosophy and the modern non-Marxist philosophy of history. The author of the article maintains that for a long time prevailing Christian historiosophy by the middle of 19th century has lived out its potentialities and has ceased to respond to the culturo-hilosophical demands of the time in Europe. The newly born multiple trends of the modern philosophy of history were characterized by subjectivistic and relativistic inclinations in the sphere of historical knowledge.